The WHO surgical safety checklist: survey of patients' views. Issue 11 (18th July 2014) - Russ, Stephanie Jane; Rout, Shantanu; Caris, Jochem; Moorthy, Krishna; Mayer, Erik; Darzi, Ara; Sevdalis, Nick; Vincent, Charles
Abstract : Background: Evidence suggests that full implementation of the WHO surgical safety checklist across NHS operating theatres is still proving a challenge for many surgical teams. The aim of the current study was to assess patients' views of the checklist, which have yet to be considered and could inform its appropriate use, and influence clinical buy-in. Method: Postoperative patients were sampled from surgical wards at two large London teaching hospitals. Patients were shown two professionally produced videos, one demonstrating use of the WHO surgical safety checklist, and one demonstrating the equivalent periods of their operation before its introduction. Patients' views of the checklist, its use in practice, and their involvement in safety improvement more generally were captured using a bespoke 19-item questionnaire. Results: 141 patients participated. Patients were positive towards the checklist, strongly agreeing that it would impact positively on their safety and on surgical team performance. Those worried about coming to harm in hospital were particularly supportive. Views were divided regarding hearing discussions around blood loss/airway before their procedure, supporting appropriate modifications to the tool. Patients did not feel they had a strong role to play in safety improvement more broadly. Conclusions: It is feasible and instructive to capture patients' views of the delivery of safety improvements like the checklist. We have demonstrated strong support for the checklist in a sample of surgical patients, presenting a challenge to those resistant to its use.